Impacts of obstacle-crossing during walking on postural control strategies in individuals with functional ankle instability - Ma, Ke; Zhou, Wenlong; Shi, Xiangwei; Wang, Guodong; Mao, Xiaokun; Kong, Lingyu; Zhang, Qiuxia (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundLateral ankle sprains often progress to functional ankle instability (FAI). Obstacle-crossing could pose greater challenges for individuals with FAI due to significant impairments in ankle kinesthesia and joint position sense. While existing studies have focused on level-ground gait characteristics in FAI, the postural control strategies underlying obstacle-crossing remain unclear, and the impact of obstacle height on these strategies has not been investigated.PurposeThis study is aimed at analyzing the postural control strategies of individuals with FAI during obstacle-crossing at different heights.MethodsTwenty-three male participants [unilateral FAI group (n = 11) and matched controls (n = 12)] were recruited. FAI was identified using the Cumberland Ankle Instability Tool (CAIT score <24). Obstacle heights were set at 0%, 10%, and 20% of individuals’ leg length (LL). Participants completed crossing tasks in randomized order. The individuals with FAI use their FAI-affected limb as the swing leg and controls use the matched limb.ResultsCompared to the control group, the FAI group exhibited smaller hip flexion angles (P = 0.008), greater trunk lateral flexion (P = 0.033), and reduced medio-lateral margin of stability (ML_MoS) at landing (P = 0.046). As obstacle height increased, the FAI group showed significant differences in ML_MoS at landing (P < 0.001), with notably lower ML_MoS when the obstacle height was set at 20% LL compared to controls (P = 0.001).ConclusionCompared to healthy individuals, those with FAI adapt movement patterns through proximal compensation strategies, characterized by compensatory trunk lateral flexion. Increased obstacle height exacerbates instability during landing, particularly at higher heights, where individuals with FAI demonstrate significantly diminished lateral stability. These findings emphasize the critical influence of FAI on balance control and adaptive postural control strategies during obstacle-crossing.